Growth of Legionella pneumophila in thioglycolate-elicited peritoneal macrophages from A/J mice. - Yamamoto, Y (1988)
Legionella pneumophila is a facultative intracellular bacterium which readily grows in cultures of guinea pig and human mononuclear phagocytes. In this report, we demonstrate that the Legionella sp. also grows in thioglycolate-elicited macrophages obtained from A/J mice but not in cells from other mouse strains tested, such as BDF1, DBA/2, C3H/HeN, C57BL/6, and BALB/c. Growth of Listeria monocytogenes and interleukin-1 production in A/J mice were similar to their growth and production in other strains tested, and the growth of Staphylococcus epidermidis was restricted by A/J macrophages. This finding suggests that although A/J macrophages share functional capabilities with cells from other mouse strains, they differ in growth restriction capacity for the Legionella sp. Resident macrophages were less permissive than were thioglycolate-elicited cells in that resident cells from A/J mice failed to support the growth of Legionella pneumophila. Also, resident cells from BDF1 mice rapidly eliminated the bacteria, rather than merely restricting growth. This finding was also observed in in vivo studies in which thioglycolate pretreatment of mice resulted in the enhanced recovery of viable bacteria from the peritoneal cavity of mice infected intraperitoneally. Higher numbers of bacteria were obtained from A/J mice and, in addition, this strain was more susceptible to the lethal effects of Legionella infection. These data suggest that, as with other intracellular bacteria, macrophages may serve a pivotal role in the early stages of Legionella infection and further suggest that the A/J mouse represents a useful animal model for the study of Legionella infection and immunity.